A Potential Integrated Water Quality Strategy for the Mississippi River Basin and the Gulf of Mexico - Suzie Greenhalgh; Paul Faeth (The Scientific World Journal)
Nutrient pollution, now the leading cause of water quality impairment in the U.S., has had significant impact on the nation’s waterways. Excessive nutrient pollution has been linked to habitat loss, fish kills, blooms of toxic algae, and hypoxia (oxygen-depleted water). The hypoxic “dead zone” in the Gulf of Mexico is one of the most striking illustrations of what can happen when too many nutrients from inland watersheds reach coastal areas. Despite programs to improve municipal wastewater treatment facilities, more stringent industrial wastewater requirements, and agricultural programs designed to reduce sediment loads in waterways, water quality and nutrient pollution continues to be a problem, and in many cases has worsened. We undertook a policy analysis to assess how the agricultural community could better reduce its contribution to the dead zone and also to evaluate the synergistic impacts of these policies on other environmental concerns such as climate change. Using a sectorial model of U.S. agriculture, we compared policies including untargeted conservation subsidies, nutrient trading, Conservation Reserve Program extension, agricultural sales of carbon and greenhouse gas credits, and fertilizer reduction. This economic and environmental analysis is watershed-based, primarily focusing on nitrogen in the Mississippi River basin, which allowed us to assess the distribution of nitrogen reduction in streams, environmental co-benefits, and impact on agricultural cash flows within the Mississippi River basin from various options. The model incorporates a number of environmental factors, making it possible to get a more a complete picture of the costs and co-benefits of nutrient reduction. These elements also help to identify the policy options that minimize the costs to farmers and maximize benefits to society.